2015
DOI: 10.1097/qad.0000000000000594
|View full text |Cite
|
Sign up to set email alerts
|

Low SAMHD1 expression following T-cell activation and proliferation renders CD4+ T cells susceptible to HIV-1

Abstract: Objectives:HIV-1 replication depends on the state of cell activation and division. It is established that SAMHD1 restricts HIV-1 infection of resting CD4+ T cells. The modulation of SAMHD1 expression during T-cell activation and proliferation, however, remains unclear, as well as a role for SAMHD1 during HIV-1 pathogenesis.Methods:SAMHD1 expression was assessed in CD4+ T cells after their activation and in-vitro HIV-1 infection. We performed phenotype analyzes using flow cytometry on CD4+ T cells from peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 43 publications
8
51
1
Order By: Relevance
“…Long-term cART will not restore this cell subset. This result is consistent with the result of another study, which revealed that SAMHD1 - activated CD4 + T cells are more permissive to HIV-1 infection and thus might lead to the loss of this cell subset in HIV-1 infected patients26. SAMHD1 is a host enzyme that participates in the metabolism of DNA via regulation of intracellular dNTP levels2.…”
Section: Discussionsupporting
confidence: 90%
“…Long-term cART will not restore this cell subset. This result is consistent with the result of another study, which revealed that SAMHD1 - activated CD4 + T cells are more permissive to HIV-1 infection and thus might lead to the loss of this cell subset in HIV-1 infected patients26. SAMHD1 is a host enzyme that participates in the metabolism of DNA via regulation of intracellular dNTP levels2.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, CCR6 + versus CCR6 -T cells stimulated via the TCR in the presence/absence of ATRA expressed decreased levels of IFN-stimulated genes, such as IFITM1, IFITM2, IFITM3, and IRF8 (Supplemental Tables 1-4), consistent with the low Th17 ability to respond to IFN (23). Finally, although differences in the expression of SAMHD1, a key IFN-induced HIV restriction factor (22,56,57), were not observed in the microarrays, in the presence/absence of ATRA, levels of SAMHD1 mRNA measured by RT-PCR were significantly lower in CCR6 + versus CCR6 -T cells (Supplemental Figure 5). This stresses the existence of false negatives in high-throughput transcriptional screenings.…”
Section: Atra Promotes a Unique Transcriptional Program Associated Wimentioning
confidence: 54%
“…( [21][22][23]. Most recently, CD4 + T cells expressing the Th17 markers CCR6 and RORγt were identified as the first targets of SIV during vaginal transmission (24); in addition, the detrimental role of viral permissive CCR6 + T cell infiltration into the gut was documented (25).…”
Section: Introductionmentioning
confidence: 99%
“…Rhesus macaques infected with a wild-type or a truncated form of Vpx that abrogates its capacity to induce SAMHD1 degradation exhibited a differential virus replication capacity and plasma viremia [56]. CD4 + T cell subsets that are more prone to HIV-1 infection showed reduced SAMHD1 levels [57]. Additionally, a subset of HIV elite controllers (EC) [58], specifically those individuals that suppress virus replication in the absence of antiretroviral therapy for a prolonged period of time, had lower SAMHD1 mRNA expression than did viremic HIV patients or seronegative healthy donors [59].…”
Section: The Role Of Samhd1 In Hiv-1 Diseasementioning
confidence: 98%